AWARENESS OF INTERFERON THERAPY AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
Interferon is perhaps the term given to antiviral material formed by many vertebrate cells in reaction to viral infections. Research has established a number of mechanisms involved, in therapeutic benefits of interferon together with antiviral, innate immunity-enhancing and cytostatic functions.This survey was performed for assessing the awareness about interferon therapy amongst dental students. A cross sectional survey was performed with a self-administered questionnaire with 10 queries circulated among 100 dental students. The questionnaire assessed the awareness about Interferon therapy,their medicinal uses,anticancer activity,mechanism of action and side effects.The responses were recorded and analysed.91% of the respondents were not aware of medical uses of Interferon therapy .93% were not aware of anticancer activity of Interferon therapy .93 % were not aware of the mechanism of action of Interferon therapy .96% were not aware of side effects of Interferon therapy. The awareness about the use of interferon therapy is very less among dental students.Increased awareness programs and sensitization programs should be conducted to improve the awareness levels.